2021
DOI: 10.1111/spol.12778
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the politics of strain: Crime and welfare in remote Indigenous Australia

Abstract: The international criminology and social policy literature have long explored possible connections between social welfare and crime. However, existing studies tend towards high-level comparisons of crime versus total aggregate welfare spend, overlooking sub-national contextual differences between and within countries. There are also few studies that deeply explore this link in the Antipodes, including in Australia: a settler colony and (neo)liberal welfare state with a recent strong coupling of punitive social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 67 publications
(136 reference statements)
0
5
0
Order By: Relevance
“…For example, other studies have noted a significant although temporary change in physical and mental health that emerged from receiving the Supplement and/or experiencing a temporary suspension of mutual obligations (Gerards & Welters, 2022). Further, prior to the Supplement, people receiving working-age payment types were highly likely to be living in poverty (Davidson et al, 2020; Temple et al, 2019). Yet, Phillips Gray and Biddle (2020) found that individuals receiving Newstart Allowance (now JobSeeker Payment) or Youth Allowance with the $550 Supplement were estimated to have had the largest reduction in household poverty, with poverty rates falling from 67 per cent to 7 per cent.…”
Section: Studying Australia's Covid-19 Basic Incomementioning
confidence: 99%
See 1 more Smart Citation
“…For example, other studies have noted a significant although temporary change in physical and mental health that emerged from receiving the Supplement and/or experiencing a temporary suspension of mutual obligations (Gerards & Welters, 2022). Further, prior to the Supplement, people receiving working-age payment types were highly likely to be living in poverty (Davidson et al, 2020; Temple et al, 2019). Yet, Phillips Gray and Biddle (2020) found that individuals receiving Newstart Allowance (now JobSeeker Payment) or Youth Allowance with the $550 Supplement were estimated to have had the largest reduction in household poverty, with poverty rates falling from 67 per cent to 7 per cent.…”
Section: Studying Australia's Covid-19 Basic Incomementioning
confidence: 99%
“…The recognition of the stalled labour market and social distancing regulations triggered by the pandemic also saw the temporary suspension of Community Development Program (CDP) activitiesa remote Work-for-the-Dole program targeting First Nations people in remote areas of Australia. CDP has been devastating for remote First Nations communities causing widespread harm to the 30,000-40,000 people forced onto the program, with its negative impacts being felt not only by program participants, but also reverberating far and wide across family and kinship networks (Jordan, 2016;Staines & Zahnow, 2021). CDP has thus been examined as an example of a policy that continues settler colonialism in Australiaboth through the material deprivation that is part of its design, its disregard for First Nations self-determination, as well as its assimilationist approach, requiring First Nations peoples to take on settler norms and livelihoods (Altman, 2018).…”
Section: Changes From the Suspension Of Mutual Obligationsmentioning
confidence: 99%
“…Emerging research suggest that despite claims from some commentators and politicians that people under CIM would use the Supplement to increase alcohol consumption, thereby increasing crime rates (Roberts, 2020), crime has either remained stable or reduced in these communities. This is partly explained from the alleviation of general strain brought about by the relaxation of mutual obligations and increases in income, which has enabled greater expenditure on food and basic goods (Markham and Kerins, 2020; Staines and Zahnow, 2021).…”
Section: Governing Unemployment Through a Public Health Crisismentioning
confidence: 99%
“…Per month rates range significantly, from $35 USD/$47 AUD (Brazilian Citizen's Basic Income), to $500 USD/$671 AUD (Stockton California trial), to $635 USD/$852 AUD (Finland), to $1,430 USD/$1,920 AUD (Germany), or $1,968 USD/ $2,643 AUD (Spain) (Samuel, 2020). As outlined earlier, a weekly income of at least $496.77 AUD ($1987.08 AUD per month) is necessary to take (single) Australians above the Henderson poverty line, but this could be met either wholly or partially by a basic income payment, which could provide either a core single payment or an unconditional extra (and thus, safety net or economic floor) to supplement ongoing unemployment and other social security benefits (Staines et al, 2021). The possibility of combining a basic income and JG may also assist in raising the income floor for unemployed peoples, while simultaneously securing the potential health and wellbeing benefits of work (Fitzroy & Jin, 2018).…”
Section: Local Control Surveillance Trust and Compliancementioning
confidence: 99%
“…The CDP has caused widespread harm, mainly due to dramatic increases in non-compliance penalty rates, which have further reduced already very low unemployment benefits (DPM&C, 2018; Jordan & Fowkes, 2016; Markham & Altman, 2019). There are frequent reports of CDP participants and their dependents going without food, struggling with housing payments, and experiencing generally poorer health and wellbeing (Jordan & Fowkes, 2016; Staines, 2018; Staines et al, 2021). The CDP has also disrupted forms of productive work that are important to maintaining wellbeing, such as care work, including caring for people, Country, culture, and community (Dudgeon et al, 2014; Gee et al, 2014; Staines, 2018; Staines et al, 2021; Yap & Yu, 2016).…”
Section: Work and Workfare In Remote Australiamentioning
confidence: 99%